2012
DOI: 10.1128/aem.02363-12
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Colonization and Shedding Patterns after Oral Challenge of Cattle with Three Escherichia coli O157:H7 Strains

Abstract: Experimental oral challenge studies with three different genotypes of Escherichia coli O157:H7 were conducted in cattle to determine the genotype-specific variability in shedding frequencies and concentrations and the frequency and extent of contamination of the environment. The results indicated that the E. coli O157:H7 genotype and ecological origin maybe important factors for the occurrence and concentration in the cattle host. Four groups of six young Holstein steers each were orally challenged with 10 6 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…Some animal to animal variation in shedding was expected because the length and intensity of fecal shedding in response to natural or experimental inoculation with E. coli O157:H7 are highly variable. [49] Overall, the decline in E. coli O157:H7 shedding following inoculation was similar to that observed in other challenge studies with E. coli O157:H7 in sheep and cattle. [19,50] Our study was designed as a proof of concept with a relatively small number of sheep (n ¼ 3 per treatment) and our findings will need to be validated in a larger animal experiment.…”
Section: Discussionsupporting
confidence: 86%
“…Some animal to animal variation in shedding was expected because the length and intensity of fecal shedding in response to natural or experimental inoculation with E. coli O157:H7 are highly variable. [49] Overall, the decline in E. coli O157:H7 shedding following inoculation was similar to that observed in other challenge studies with E. coli O157:H7 in sheep and cattle. [19,50] Our study was designed as a proof of concept with a relatively small number of sheep (n ¼ 3 per treatment) and our findings will need to be validated in a larger animal experiment.…”
Section: Discussionsupporting
confidence: 86%
“…Cattle generally remain asymptomatic but they may shed the bacteria into the environment (Gansheroff and O'Brien 2000;Pruimboom-Brees et al 2000;Lim, Yoon and Hovde 2010;Nguyen and Sperandio 2012). Among cattle, shedding occurs intermittently (Hancock et al 1997;Kulow et al 2012;Sharma et al 2012), and it was reported that, at any time, up to 50% of the healthy animals excrete E. coli O157:H7 in their stool (Lim, Yoon and Hovde 2010). Large variations have been described in the shedding patterns of individual animals, the proportion of shedding animals on farms that harbor them and, over time, in the amount of shedding on the same farm (Smith, Paiba and Ellis-Iversen 2010).…”
Section: Epidemiology Of Escherichia Coli Shedding By Cattlementioning
confidence: 99%
“…Twenty-two Holstein steers, aged 6–7 months, were selected for the transmission experiment. These steers had been used previously in a separate study involving single strain challenge experiments with one of three strains of ECO157 (but no infection transmission among animals) [ 24 ] and they were reused in the current experiment for ethical reasons (to minimize the number of animals to be sacrificed). Moreover, the experimental design partially controlled for the confounding effect of host factors which might have been introduced by enrolment of different animals.…”
Section: Methodsmentioning
confidence: 99%
“…Each of the 12 steers was inoculated by mixing 1 ml inoculum with ~10 ml clean tap water in a drinking cup. A procedure described previously [ 24 ] was followed to ensure the inoculum was consumed. The infection status of the inoculated steers was determined 1 day post-inoculation (p.i.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation